Disclosure and help seeking behavior of women exposed to physical spousal violence in Dhaka slums - Kausar Parvin; Naznin Sultana; Ruchira Tabassum Naved (BMC, 2016)
Abstract Background Despite high prevalence of intimate partner violence (IPV) and its adverse social and health consequences, the rate of help seeking for IPV is generally low. Although the level of IPV is much higher in urban slums of Bangladesh, the level and nature of help seeking of the victims are unknown. This paper aims to address this gap in the literature. Methods Using a cross-sectional survey conducted between August 2011-February 2012, we explored disclosure of violence, help seeking behavior, and their correlates among randomly selected currently married women aged 15-29 in Dhaka slums (n = 2604). Results About 60 % of the currently married women reported past year spousal physical violence, but only 21 % disclosed and 19 % sought any help. High acceptance of violence was the main reason for not seeking help. Help was most commonly sought from informal sources (89 %). Any education, frequent and severe physical abuse, and presence of children increased the likelihood of disclosure and help seeking. Most survivors from slum who disclosed also sought help. Conclusions Despite widespread physical abuse, many survivors never sought help. Wide acceptance of violence hampering help seeking needs to be challenged. Increasing disclosure would also enhance help seeking. Awareness rising regarding rights of women to live a violence free life is essential. Although many services are available in the urban area, information about these services needs to be available to women. Promoting education is important in increasing both disclosure and service uptake.